The Role of Pensioners in Sustainable Development: The case of Qassim Area (Buraidah, Onaizah, Al- Rass) Kingdom of Saudi Arabia - AL- bassam, Ahmad Mohammad (Journal of Humanities & Social Sciences, 2020)
This study aimed to identify the role of pensioners in sustainable development in Qassim area (Buraidah, Onaizah and Al- Rass). The study used the descriptive analytical approach to achieve the main objectives. In order to achieve the study objectives; the sample was selected randomly; It has been relying on a survey sample consists of (377) questionnaires. A set of statistical methods applied, compatible with the requirements, objectives and questions of the study. The study has found that; most pensioners are married, educated (69 %), have a fairly high income, and their type of home is a villa. The results of the study revealed that; the results of the analysis of the mono- variance (ANOVA) showed that; there were statistically significant differences at (α = 0.05), among the opinions of the individuals of the sample of the three cities for each axis, with statistically significant at (0.00), and that one of the most important causes of retirement is not to reconcile the profession and private life, and the large additional burdens. One of the most important problems which face the pensioners after retirement is that; the pension is not enough for life requirements, they suffer after retirement from a large non- invested spare time, and the most important advantages and experiences post- retirement that; it enabled them to take care of the family and gave them opportunities to try with other work and activities with statistically significant. The Schiff test showed that; the sample individuals in the three cities strongly agree with these terms, especially the sample of the city of Onaizah and Al- Rass.